Status Epilepticus Following Intrathecal Administration of Bupivacaine: A Case Report - Arthur Vanmarcke; Piet Lormans; Catherine Vandewaeter (SAGE Publishing, 2022)
Spinal anesthesia is common practice and rarely causes complications. Although extended experience is present, seldom side effects of this technique and the administration of intrathecal local anesthetics and/or opioids can occur. We present a case in which a 76-year old woman undergoing total hip arthroplasty received a low dose of intrathecal bupivacaine and sufentanil. One hour after administration, she developed myoclonic seizures of the lower extremities followed by generalized tonic-clonic seizures and status epilepticus. We conclude that status epilepticus is a rare and possible lethal side effect of intrathecal bupivacaine. Symptoms may be misleading, highlighting the importance of early recognition and adequate management.